Sorosi Kaasaegse Kunsti Eesti Keskus 1993-1998. - Helme, Sirje (Tallinn : Soros Center for Contemporary Arts, 1998)
Toomik, Jaan ; Lapin, Leonhard ; Ojaver, Jüri ; Keskküla, Ando ; Pere, Peeter ; Siib, Liina ; Raidmets, Toivo ; Viljus, Mart ; Kõresaar, Andrus ; Tralla, Mare ; Juurak, Anu ; Kuusing, Kai ; Kelomees, Raivo ; Kivisildnik, Kodumaa ; Kaljo, Kai
Engels & Ests
boek
Keywords: Estland